2015
DOI: 10.1002/ange.201503041
|View full text |Cite
|
Sign up to set email alerts
|

A Cell‐Permeable ATP Analogue for Kinase‐Catalyzed Biotinylation

Abstract: ATPanalogues have been powerfulcompounds for the study of kinase-catalyzed phosphorylation. However,t he cell impermeability of ATPanalogues has largely limited their use to in vitro lysate-based experiments.H erein, we report the first cell-permeable ATPa nalogue,A TP-polyamine-biotin (APB). APB is shown to promote biotin labeling of kinase substrates in live cells and has future applications in phosphoprotein purification and analysis.More generally,these studies provideafoundation for the development of add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 44 publications
0
4
0
1
Order By: Relevance
“…A fully orthogonal system-in which the engineered enzyme utilizes the bumped substrate analog with high efficiency, while no longer recognizing the native substrate-may also benefit from a high signal-to-noise ratio. The bump-hole strategy has been successful with other enzyme families, including kinases, 30,31 acetyltransferases, 32 methyltransferases, 33 and ADPribosyltransferases. 34 Previous studies have demonstrated that glycosyltransferases are amenable to enzyme-substrate engineering, wherein the active site is modified to accept a non-native substrate.…”
Section: Introductionmentioning
confidence: 99%
“…A fully orthogonal system-in which the engineered enzyme utilizes the bumped substrate analog with high efficiency, while no longer recognizing the native substrate-may also benefit from a high signal-to-noise ratio. The bump-hole strategy has been successful with other enzyme families, including kinases, 30,31 acetyltransferases, 32 methyltransferases, 33 and ADPribosyltransferases. 34 Previous studies have demonstrated that glycosyltransferases are amenable to enzyme-substrate engineering, wherein the active site is modified to accept a non-native substrate.…”
Section: Introductionmentioning
confidence: 99%
“…To improve the cell permeability of the ATP probe, Pflum and co-workers developed an analog 6. 26 The improved cell permeability of this probe was ascribed to the partial neutralization of the triphosphate's negative charge with a cationic polyamine linker, methylated spermine. The difference between the identity of proteins biotinylated in the cell vs lysate demonstrates the significance of the environment on the phosphorylation process, indicating the influence of compartmentalization inside the cell.…”
Section: Journal Of Medicinal Chemistrymentioning
confidence: 99%
“…The difference between the identity of proteins biotinylated in the cell vs lysate demonstrates the significance of the environment on the phosphorylation process, indicating the influence of compartmentalization inside the cell. 26 Ferrocene-modified bioconjugates are popular redox reporters thanks to their electrochemical properties and stability in aqueous solution. 32 Kraatz and co-workers have developed γferrocene-modified ATP derivatives 7−10 for monitoring protein kinase activity and for inhibitor screening.…”
Section: Journal Of Medicinal Chemistrymentioning
confidence: 99%
“…ABPP probes covalently target the active site of enzymes for their detection or purification. Substrate ID describes a set of tools for the capture of the downstream substrates of a given enzyme . While ABPP and substrate ID are powerful tools for assessing the functional status and output of enzymes, we sought a way to not only identify active kinases but also to capture the kinases as they bind to a specific substrate, a method we term substrate‐based protein profiling (SBPP).…”
Section: Introductionmentioning
confidence: 99%